Physical Condition Analysis of Professional Football Players - Nidomuddin, Muhammad; Pamungkas, Hari; Yusuf, Havid; Husen, Ashari; Prasetiyo, Rahayu (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2023)
This study aims to determine the level of physical condition level in Nusantara FC players. this research uses descriptive research. Data were analyzed using quantitative analysis in the form of percentages. The population and samples in this study are Nusantara FC totaling 23 professional players who play in League 2 Indonesia. Average physical condition of Nusantara FC players. Speed gets an average result of 4.29, endurance with an average of 56.49 with a lesser category, explosive power gets an average result of 56 with a good category, average flexibility of 19.3 with a good category, and average agility of 7.99 with a good category. The percentage of the physical condition of the players is as follows; speed gets results with a percentage of 78.2% in the good category. The percentage of endurance results is 64% in the less category. Explosive power is 64% with a good category. The results of flexibility with a percentage of 60.8% in the good category. Agility with a percentage of 39.1% in the good category. Analysis of the results of physical conditions is an important part of professional soccer in improving the quality of techniques and tactics in the matches carried out.